Optional problem solving in peer-to-peer lending - Putri Wardhani; Nynda Fatmawati Octarina (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This study aims to find alternative solutions to peer-to-peer lending problems. This study uses a normative juridical approach. The data collection technique used is documentation technique (scientific journal articles related to peer-to-peer lending). The data analysis technique used is analytical descriptive analysis regarding default settlement options in peer-to-peer lending. The results of this study indicate that alternative solutions for solving peer-to-peer lending problems are based on Article 21 POJK No. 77/POJK.01/2016 the parties are required to mitigate risks through litigation channels, namely by going to court on the basis of default (Article 1243 Civil Code) made by the recipient of the loan; and the non-litigation route, namely through mediation because mediation efforts are included in the substance of the law (Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution).